A sophisticated, differentiated Golgi in the ancestor of eukaryotes - Barlow, Lael D. (BMC Biol, 2018)
BACKGROUND: The Golgi apparatus is a central meeting point for the endocytic and exocytic systems in eukaryotic cells, and the organelle’s dysfunction results in human disease. Its characteristic morphology of multiple differentiated compartments organized into stacked flattened cisternae is one of the most recognizable features of modern eukaryotic cells, and yet how this is maintained is not well understood. The Golgi is also an ancient aspect of eukaryotes, but the extent and nature of its complexity in the ancestor of eukaryotes is unclear. Various proteins have roles in organizing the Golgi, chief among them being the golgins. RESULTS: We address Golgi evolution by analyzing genome sequences from organisms which have lost stacked cisternae as a feature of their Golgi and those that have not. Using genomics and immunomicroscopy, we first identify Golgi in the anaerobic amoeba Mastigamoeba balamuthi. We then searched 87 genomes spanning eukaryotic diversity for presence of the most prominent proteins implicated in Golgi structure, focusing on golgins. We show some candidates as animal specific and others as ancestral to eukaryotes. CONCLUSIONS: None of the proteins examined show a phyletic distribution that correlates with the morphology of stacked cisternae, suggesting the possibility of stacking as an emergent property. Strikingly, however, the combination of golgins conserved among diverse eukaryotes allows for the most detailed reconstruction of the organelle to date, showing a sophisticated Golgi with differentiated compartments and trafficking pathways in the common eukaryotic ancestor. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12915-018-0492-9) contains supplementary material, which is available to authorized users.